Formulação de bloco intertravado cerâmico com adição de resíduos urbanos e industriais - Santos, Osvaldo Cruz (2013)
The production of waste from urban and industrial activities is one of the factors of environmental contamination and has aroused attention of the scientific community, in the sense of its reuse. On the other hand, the city of Salvador/Ba, with approximately 262 channels, responsible for storm water runoff, produces every year, by the intervention of cleaning and clearing channels, a significant volume of sediments (dredged mud), and thus an appropriate methodology for their final destination. This study aims to assess the influence of incorporation of these tailings in arrays of clay for production of interlocked block ceramic, also known as ceramic paver. All the raw materials from the metropolitan region of Salvador (RMS) were characterized by x-ray fluorescence, x-ray diffraction, thermal analysis (TG and TDA), particle size analysis and dilatometry. With the use of statistical experimental planning technique, ternary diagram was defined in the study region and the analyzed formulations. The specimens were prepared with dimensions of 60x20x5mm³, by uniaxial pressing of 30 MPa and after sintering at temperatures of 900°, 1000º and 1100ºC the technological properties were evaluated: linear shrinkage, water absorption, apparent porosity, apparent specifies mass, flexural rupture and module. For the uniaxial compression strength used cylindrical probe body with Ø 50 mm. The standard mass (MP) was prepared with 90% by weight of clay and 10% by weight of Channel sediment (SCP), not being verified significant variations in the properties of the final product. With the incorporation of 10% by weight of manganese residue (PFM) and 10% by weight of the Ceramic waste (RCB) in the mass default, in addition to adjusting the plasticity due to less waste clay content, provided increased linear firing shrinkage, due the significant concentration of K2O, forming liquid phase at low temperature, contributing to decreased porosity and mechanical resistance, being 92,5 MPa maximum compressive strength verified. After extract test leachate and soluble, the piece containing 10% of the PFM, was classified as non-hazardous and inert material according to NBR10004/04 ABNT. The results showed the feasibility on using waste, SCP, RCB and PFM clay mass, at temperatures above 900ºC, paver ceramic production, according to the specifications of the technical standards, so that to exceed the 10% of the PFM, it becomes imperative to conduct studies of environmental impacts